Study of calcitriol anti-aging effects on human natural killer cells in vitro. Issue 1 (1st January 2021) - Li, Weiran; Che, Xu; Chen, Xuemei; Zhou, Meiling; Luo, Xiaoping; Liu, Tao
ABSTRACT: Vitamin D is widely considered to have a regulatory effect on the immune system. Some clinical investigations have shown that the demand for vitamin D increases with age. Calcitriol is the biologically active form of vitamin D. However, its effect on human natural killer (NK) cells remains unclear. Therefore, in this study, we investigated the anti-aging and immunomodulatory effects of calcitriol on NK cells using a series of immunological methods to explore its important role in innate immunity. We found that calcitriol reversed the expression of aging-related biomarkers in NK cells and inhibited their expansion by maintaining these cells in the G1 phase, without any apoptosis and exhaustion. Calcitriol repressed the release of inflammation-related cytokines, such as interleukin-5 (IL-5), interleukin-13 (IL-13), interferon-gamma (IFN-γ), and tumor necrosis factor-alpha (TNF-α). The degranulation of NK cells was downregulated by calcitriol when these cells were co-cultured with K562 tumor cells. We also found that calcitriol upregulated the aging-related sirtuin 1- protein/kinase R-like endoplasmic reticulum kinase (SIRT1/pERK) pathway and SIRT1-deltaExon8 (SIRT1-∆Exon8) expression by activating the vitamin D receptor (VDR). Moreover, calcitriol could be a potential negative regulator of NK cell apoptosis and mitochondrial inactivation which caused by oxidative stress. Thus, calcitriol exhibits anti-aging effects on human NK cells in vitro by activating the SIRT1-PERK axis and resisting oxidative senescence.